Streptozotocin-induced rodent models of diabetes: Protocol comparisons - Samuel, Renata O. [UNESP]; Gomes-Filho, Joäo E. [UNESP]; Dezan-Júnior, Eloi [UNESP]; Cintra, Luciano T.A. [UNESP] (My University, 2014)
Type 1 and type 2 diabetes mellitus (DM) are characterized by hyperglycemia, due to lost or damaged insulin-producing β-cells within the pancreatic islets of Langerhans. Rodent models of DM result in hyperglycemia, arising from different forms of islet deterioration. Streptozotocin (STZ) is currently used to induce experimental DM in rodents because it selectively targets pancreatic β-cells. STZ enters β-cells via a glucose transporter (GLUT2), causing DNA alkylation, which in turn activates poly ADP-ribosylation, leading to ATP depletion and resulting in the formation of superoxide anions. Concomitantly, STZ triggers nitric oxide formation, which results in DNA damage. Both of these actions cause β-cell necrosis, leading to DM. These features provide a methodological advantage for STZ, resulting in the development of human-like DM. However, there is no consensus across the literature regarding the optimal STZ dose or administration route for developing rodent models of DM. In addition, the nutritional status of the animals employed has also been shown to influence outcomes. This review aims to compare the different methodologies, considering their advantages and disadvantages.
Keywords: mice; rat; Rodent models; Streptozotocin